The larva of Rhyacophila hartigi Malicky 1971, including a discriminatory matrix to the Italian Rhyacophila larvae with tufted multifilament gills (Rhyacophilidae, Trichoptera) - Waringer, Johann; Malicky, Hans (Zootaxa, 2020)
The collection of adults and larvae sampled at the same site on Sicily and the absence of confusing species at the sampling location enabled a description of the hitherto unknown larva of Rhyacophila hartigi Malicky 1971 (Trichoptera: Rhyacophilidae). We present information on the morphology of the larva and illustrate the most important diagnostic features. This dataset is included in a discriminatory matrix of the ten other Rhyacophila larvae with tufted multifilament gills of Italy described so far. Species can be separated by coloration patterns of head and pronotum, and by anal claw morphology; however, separation of the R. dorsalis-palmeni-simulatrix-vulgaris species quartet is not yet possible. Rhyacophila hartigi is restricted to the southern Apennine Peninsula and the island of Sicily (Cianficconi et al. 2008).